Correlation between the Atherogenic Index of Plasma and Progression of Non-target Lesion Vascular Disease Following Percutaneous Coronary Intervention using Drug-eluting Stents - Hou, Tian-Hua; Wang, Fei; Hao, Cui-Jun; Zhang, Chong; Ning, Meng; Chen, Yi; Wang, Kun; Liu, Ying-Wu (Current Pharmaceutical Design, 2024)
ObjectiveTo examine the correlation between Atherogenic Index of Plasma (AIP) levels and the progression of non-target lesion vascular disease following the deployment of Drug-eluting Stents (DES).MethodsWe retrospectively enrolled patients who had undergone successful treatment for CAD with DES and subsequently underwent a coronary angiography follow-up at the Cardiology Department of Tianjin Third Central Hospital from January 2017 to July 2022. The annual change in Gensini Score (GS) was calculated according to two angiographic evaluations in order to assess the progression of non-target lesion vascular disease; a change greater than 1 indicated progression, while a change of 1 or less indicated stability. AIP was calculated according to serum lipid parameters. Multivariate Logistic regression model was used to evaluate the relationship between AIP level and progression of non-target coronary artery lesions. The ROC curve analysis was performed to evaluate the diagnostic value of AIP for coronary artery non-target lesion vascular disease progression.ResultsOut of the 344 patients who were monitored over a median duration of 1.2 years, 113 exhibited progression of non-target lesion vascular disease. Initially, baseline AIP levels were notably higher in the progression group compared to the non-progression group (0.30 [0.14, 0.43] vs. 0.11 [-0.06, 0.31]), and this difference remained significant during the follow-up period (0.19 [0.06, 0.34] vs. 0.11 [-0.06, 0.22]). Multivariate logistic regression revealed that AIP is an independent predictor for the progression of non-target lesion vascular disease following DES treatment. Individuals in the highest tertile of AIP faced a considerably elevated risk compared to those in the lowest tertile (OR = 4.88, 95% CI: 2.12-11.21, P < 0.001). Moreover, utilizing receiver operating characteristic curve analysis, a 0.15 AIP level cut-off was determined for diagnosing disease progression, with a sensitivity of 73.5% and specificity of 56.7%, and an area under the curve of 0.672 (95% CI: 0.613-0.731, P < 0.01).ConclusionAIP significantly correlates with the progression of non-target lesion vascular disease among patients with coronary artery disease who have undergone DES treatment, establishing itself as an independent risk factor in addition to conventional predictors.
Keywords: non-target lesion vascular disease